2018
DOI: 10.1093/jpids/piy103
|View full text |Cite
|
Sign up to set email alerts
|

Change in Bacterial Causes of Community-Acquired Parapneumonic Effusion and Pleural Empyema in Children 6 Years After 13-Valent Pneumococcal Conjugate Vaccine Implementation

Abstract: We describe here changes in the bacterial causes of pleural empyema before and after implementation of the 13-valent pneumococcal conjugate vaccine (PCV13) program in France (2009–2017). For 220 (39.3%) of 560 children, a bacterial cause was found. The frequency of pneumococcal infection decreased during the study from 79.1% in 2009 to 36.4% in 2017 (P < .001). Group A streptococcus is now the leading cause of documented empyema (45.5%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
25
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 12 publications
5
25
2
2
Order By: Relevance
“…S. pneumoniae was the most frequently identified pathogen, followed by S. pyogenes and S. aureus , which is in agreement with previously published data on the etiology of PPE/PE in children worldwide [26,28,31,32,33,34,35,36]. The study period covered the introduction of PCVs in Switzerland among all children <2 years of age (with a catch-up dose up to five years of age) with PCV7 in 2006 and a switch to PCV13 in 2011 [17].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…S. pneumoniae was the most frequently identified pathogen, followed by S. pyogenes and S. aureus , which is in agreement with previously published data on the etiology of PPE/PE in children worldwide [26,28,31,32,33,34,35,36]. The study period covered the introduction of PCVs in Switzerland among all children <2 years of age (with a catch-up dose up to five years of age) with PCV7 in 2006 and a switch to PCV13 in 2011 [17].…”
Section: Discussionsupporting
confidence: 91%
“…Our data confirm that empirical antibiotic treatment must target S. pneumoniae and cover S. pyogenes and S. aureus [11,28,35]. The choice of the empirical antibiotic agent should be guided by local resistance data and the emergence of resistant organisms [11].…”
Section: Discussionsupporting
confidence: 60%
“…Almost 60% of children (38/64) developed complications, mainly pleural effusion/empyema (34/64, 53%). Twenty-nine patients [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31], p = 0.015) and had a longer hospital stay (17 [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] days vs. 4.5 [1][2][3][4][5][6][7], p < 0.001).…”
Section: Resultsmentioning
confidence: 98%
“…The introduction of pneumococcal conjugate vaccines (PCV) has led to a substantial reduction of invasive pneumococcal disease and community-acquired pneumococcal pneumonia (9)(10)(11)(12). However, their impact in pediatric CAP caused by other bacteria has been barely analyzed (13,14). The aims of this study were to describe the characteristics of microbiologically confirmed hospitalized bacterial CAP in a setting with high PCV coverage, to compare outcomes according to causative bacteria and to analyze epidemiological changes over time.…”
Section: Introductionmentioning
confidence: 99%
“…The effectiveness and impact of the 13-valent pneumococcal conjugate vaccine (PCV13) against serotype 3 Streptococcus pneumoniae (ser3) has been repeatedly questioned [1][2][3][4][5]. Ser3 pneumococcus has established itself as one of the leading causes of invasive pneumococcal disease (IPD), even in the post-PCV13 introduction period (post-PCV13) [6], and has been associated with complicated and severe infections in children [5,[7][8][9]. This aggressive behavior can be firstly attributed to microbiological features of the pathogen-like thick polysaccharide capsule [10].…”
Section: Introductionmentioning
confidence: 99%